2020
DOI: 10.30994/sjik.v9i2.392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mothers' Attitudes with Diarrhea Prevention in Toddlers

Abstract: The prevalence of diarrhea diseases is increasing, the total cases of diarrhea diseases listed in the Work Area Air Lais sub-district Community Health centers Padang Jaya in 2014 reached 230 cases. The purpose of this research is to determine the relationship between mothers’ attitudes with prevention of diarrhea disease in toddlers. This research is a quantitative research with cross sectional design. The sample in this study were mothers with children under five by purposive sampling technique. The participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
0
1
0
1
Order By: Relevance
“…Stunting can be directly caused by food intake and the occurrence of infectious diseases where these two factors are greatly influenced by mother's parenting style. [24] Parenting style for children are influenced by the mother's understanding of receiving information. Parenting has a role in the nutritional status of children under 5 because food intake is usually regulated by the mothers.…”
Section: Relationship Between Parenting Style and Stunting Incidentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stunting can be directly caused by food intake and the occurrence of infectious diseases where these two factors are greatly influenced by mother's parenting style. [24] Parenting style for children are influenced by the mother's understanding of receiving information. Parenting has a role in the nutritional status of children under 5 because food intake is usually regulated by the mothers.…”
Section: Relationship Between Parenting Style and Stunting Incidentsmentioning
confidence: 99%
“…This is in line with the results of research by Permatasari, which showed that the dominant factor influencing the incidence of stunting was parenting style (OR: 6.496 95% CI: 2.486-16.974). [24] Research by also stated that there is a significant relationship between maternal parenting in feeding and the incidence of stunting. [25] Based on the results of interviews in this study, many mothers did not exclusively breastfeed their children and some mothers also only breastfeed for less than 2 years, while 1,000 HPK (First Day of Life) is a very important for the growth of children, some mothers also let their children not wear footwear when playing outside, some of them also rarely go to the posyandu so that some of them have not received complete basic immunization, and the mother's lack of attention to the food consumed by children.…”
Section: Relationship Between Parenting Style and Stunting Incidentsmentioning
confidence: 99%
“…Pendidikan Islam tradisional tertua dan sudah menjadi ciri khas yang eksistensinya teruji oleh sejarah hingga kini. Munculnya pondok pesantren tidak terlepas dari proses islamisasi masyarakat Indonesia untuk memahami dan mengamalkan ajaran Islam dalam kehidupan lebih menekankan pentingnya Islam sebagai pedoman hidup (Ridawati, 2020).…”
Section: Kajian Teoriunclassified
“…Mothers are the figures closest to toddlers. One important knowledge for mothers is how to treat toddlers with diarrhea by preventing and dealing with dehydration by giving substitute liquids [8,12,13].…”
Section: Introductionmentioning
confidence: 99%